A Critique of the Methodology on the Book Introduction to Iranian Crafts Workshops - Samira Arab; Seyyed Abdul Majid Sharifzade (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Sassanid era is one of the most important periods in Iranian history, with remarkable works of art from this period. The decorative elements in the artworks of this period indicate the connection of beliefs and beliefs in human thought. The book “Investigation of Sassanid Steel Utensils from a Symbolic Viewpoint” was published by Neda Akhavan Aghdam in 1396 in the Academy of Art Publications. Besides the lack of a coherent order for the analysis of motifs, this book has also some form and content shortcomings. The present study, based on the library method, has critically criticized the book and evaluated its form and scientific content. In this regard, the deficiencies and critical comments of each of the topics are expressed below. Referring to the shortcomings aims to understand the concepts and to explain the symbolic aspects of motifs in Sasanian metal containers which are the results of this paper.